Modelo de planeación estratégica comunitaria aplicado al ecoturismo: Caso: cooperativas turísticas de Nayarit, México. - Sosa, Maria Cristina; Brenner, Ludger (RITUR - Revista Iberoamericana de Turismo, 2023)
Community participation in decision-making constitutes an important challenge for the management of community tourism. This article aims to contribute to the understanding of community participation in ecotourism decision-making, providing a tool for studying and conducting the decision-making process in communities. A community strategic planning model is designed and applied to measure the degree of involvement of local residents in three types of decision and the performance of a set of factors considered key for active participation. The research uses a mixed approach to compare and explain the differences between two local cooperatives on the coast of the state of Nayarit, located in the west of Mexico. The result of a structured survey shows statistically significant differences in the involvement of partners in decisions, as well as in the factors that favor their participation; in-depth interviews with partners and external informants, documentary review and non-participant observation -as part of the qualitative techniques- help to explain these differences. Finally, positive bivariate correlations obtained between the variables under study and a multiple correlation coefficient of 0.80 allow us to conclude that the degree of local participation in the entire decision-making process can be explained by the interaction of seven factors analyzed, of which Learning Spaces and Leadership have the greatest impact.